Savoring Interventions Increase Positive Emotions After a Social-Evaluative Hassle - Klibert, Jeffrey J.; Sturz, Bradley R.; LeLeux-LaBarge, Kayla; Hatton, Arthur; Smalley, K. Bryant; Warren, Jacob C. (Frontiers in Psychology, 2022)
Achieving a high quality of life is dependent upon how individuals face adversity. Positive psychological interventions are well-suited to support coping efforts; however, experimental research is limited. The purpose of the current research was to examine whether different savoring interventions could increase important coping resources (i.e., positive emotions) in response to a social-evaluative hassle. We completed an experimental mixed subject design study with a university student sample. All participants completed a hassle induction task and were then randomly assigned into different intervention groups. Positive emotion ratings were collected at three points in time (baseline, post-induction task, post-intervention). Results revealed a significant time x intervention interaction effect, such that individuals in the savoring the moment intervention reported higher levels of positive emotions (at post-intervention) compared to individuals assigned to the true control group, guided imagery control group, and savoring through reminiscence intervention. Such findings represent a significant extension to savoring theory and offer support for savoring the moment exercises as a primary prevention strategy to bolster effective responses to social-evaluative hassles.